2018
DOI: 10.3390/ma11122351
|View full text |Cite
|
Sign up to set email alerts
|

Residual Tensile Strength of the Multi-Impacted Scarf-Repaired Glass Fiber-Reinforced Polymer (GFRP) Composites

Abstract: The effect of multiple/repeated impacts on a repaired composite was investigated using a low-velocity impact test. The composite samples were fabricated through a vacuum resin infusion method (VARI) and repaired by a scarf repair technique. Later, a repeated low-velocity impact test was performed on the original and repaired composites samples. Performance of the multi-impacted repaired and original samples was evaluated and compared by measuring maximum contact force, maximum displacement, maximum time durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Different authors have used this technique to estimate and compare the damaged area. Similar results were reported when compared with other complex and expensive techniques [ 26 , 38 ]. To calculate the damaged area, a MATLAB routine was specifically developed.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Different authors have used this technique to estimate and compare the damaged area. Similar results were reported when compared with other complex and expensive techniques [ 26 , 38 ]. To calculate the damaged area, a MATLAB routine was specifically developed.…”
Section: Methodssupporting
confidence: 87%
“…Fiber breakage mainly occurs at the impact face by compression and buckling, and at the back face as a consequence of tensile stress. Delamination and matrix cracking take place in the matrix, as reported by Robinson et al [ 25 ] and Kumari et al [ 26 ]. This means that the impact properties are strongly dominated by the matrix and influenced by its mechanical properties and possible defects.…”
Section: Introductionmentioning
confidence: 73%
“…Generally, the resistance of material under the cyclic loading is quantified by the residual strength model. [42][43][44][45] Residual strength is defined as the ability of GFRP to resist the cyclic loading at a given service time. In engineering applications, the strength degradation law of GFRP plays a key role in reliability assessment.…”
Section: Residual Strength Model Of Gfrp Based On Sds Principlementioning
confidence: 99%
“…It has been shown that a decrease in scarf angle as well as an increase in external reinforcement plies on the surface of a repair leads to an increase in failure loads [ 14 , 15 , 16 , 17 , 18 , 19 ]. In practice and in the literature, a scarf ratio of 1:50 has been shown to be a good compromise between repair size and properties, with 70–80% static tensile strength restoration and over 80% post-impact residual tensile strength [ 3 , 12 , 20 ]. As a scarf patch carries the load of a post-repaired component, it has been shown to be most effective when the repair and parent ply stacking sequence are equivalent.…”
Section: Introductionmentioning
confidence: 99%